Recommendations for Measurement of Child Health Literacy: A Pragmatic Approach - Hannah G. Lane; Linda Aldoory (SLACK Incorporated, 2019)
Health literacy (HL) has been well-studied in adults; however, the literature on HL in children and adolescents has only recently burgeoned. Many authors argue child and adolescent HL is unique from adult HL and should be independently measured (Bröder et al., 2017; Guo et al., 2018; Okan et al., 2018; Ormshaw, Paakkari, & Kannas, 2013; Rothman et al., 2009; Velardo & Drummond, 2017; Wharf Higgins, Begoray, & MacDonald, 2009); however, there is a lack of consensus on the best framework and practice for this measurement. Although many current HL measures are validated for use among a broad range of children and adolescents (age 7-18 years) (Guo et al., 2018; Manganello et al., 2017; Okan et al., 2018; Ormshaw et al., 2013), these measures are insufficient.